ANALISIS KESELAMATAN DAN KESEHATAN KERJA PADA BAGIAN PRODUKSI MENGGUNAKAN METODE 5S DALAM KONSEP KAIZEN DI PT. SWABINA GATRA - Ikhwatun Khasanah; Akhmad Wasiur Rizqi; Hidayat (Jurnal Rekavasi, 2022)
Occupational Health and Safety (K3) is a branch of science and application that studies how to prevent accidents in the workplace. One of the companies closely related to this program is PT. Swabina Gatra. Where this company is engaged in the manufacturing business in the form of "Packaged Drinking Water (AMDK)" with the brand "SWA". The problem that often occurs in this company is that the number of work accidents is still quite high. From the results of the study, the highest accident rate (incidence rate) occurred in 2018 with a figure of 5.67% for the last five years. Thus the proposed improvement that can be given using the 55 method in the kaizen concept is Seiri (Concise/Sorting) that is by applying sorting to items that are no longer used to make it easier to search when they will be reused. Seiton (Neat/Arrangement) that is by arranging things according to their place so that they are not scattered and look neat. Seiso (Cleaning/Cleaning) is by implementing a routine cleaning schedule for workers at each work station. Seiketsu (Treatment/Consolidation) is by applying employee discipline at work and implementing the appropriate Kaizen system. Shitsuke (Diligent / Refraining) is by enabling employees to consult when working with supervisors and the company should have a periodic schedule to conduct 5S/5R audits.